PENGARUH MODEL PEMBELAJARAN KOOPERATIF TYPE INSIDE-OUTSIDE-CIRCLE TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI RA AT-TAQWA PENGALIHAN KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR - Leni, Novita Ade; Zulkifli N, Zulkifli N; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The porpuse of this research is to investigate the influence of cooperative learning type inside-outside-circle toward child’s speaking ability 5 to 6 years old. This research was done at RA At-Taqwa Pengalihan, Enok sub - district Indragiri Hilir. The is experiment research design by one group pre-test post-test design. The population is the children at RA At-Taqwa pengalihan, Enok sub- district Indragiri Hilir regency by the total is 15 children. The technique collection data is observation. Based on the hypothesis test the score tcount is 29,45 >t table =2,145 bysig 0,000, because sig < 0.05 then there is a difference between the abiliy to speak a child of the age of the year. There is influence of cooperative learning type inside-outside-circle toward child’s speaking ability 5 to 6 years old at RA At-TaqwaPengalihan, Enok sub - district Indragiri Hilir regency is 29, 45%.Keywords: Speaking Ability, Cooperative Learning Type Inside-Outside-Circle